Analisis Penerapan Kurikulum Merdeka Dalam Membentuk Karakter Siswa - Nurila Azura; Ryanie Ibti Sania; Agus Lestari (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
This study aims to initiate how the Independent Curriculum is implemented as a strategic effort in shaping the character of students in the school environment. This curriculum is designed as a solution to the previous education system which was considered less flexible, by providing more freedom for students to develop their potential, think critically, and create innovation through diverse and student-centered learning approaches. One of the main elements of the Independent Curriculum is the use of project-based learning methods aimed at strengthening the Pancasila Student Profile. This profile includes core values ​​such as religiosity, independence, mutual cooperation, global diversity insight, and critical reasoning skills. In its implementation, the Independent Curriculum also emphasizes character formation through three main approaches, namely classroom learning activities, strengthening school culture, and community involvement. Character formation is not only carried out through open materials, but also through various activities outside the classroom such as co-curricular and extracurricular programs that instill moral and social values. The process of character formation of students is designed systematically and continuously by combining cognitive, emotional, and motor aspects, so as to produce graduates who are not only academically intelligent, but also have a strong personality and good morals. Based on the results of this study, the Independent Curriculum has significant potential in creating a more comprehensive and relevant education system to the needs of the times.